Credible deviations from signaling equilibria - Péter Eső; James Schummer (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2005)
In games with costly signaling, some equilibria are vulnerable to deviations which could be unambiguously interpreted as coming from a unique set of Sender-types. This occurs when these types are precisely the ones who gain from deviating for any beliefs the Re-ceiver could form over that set. We show that this idea characterizes a unique equilibrium outcome in two classes of games. First, in mono-tonic signaling games, only the Riley outcome is immune to this sort of deviation. Our result therefore provides a plausible story behind the selection made by Cho and Kreps' (1987) D1 criterion on this class of games. Second, we examine a version of Crawford and Sobel's (1982) model with costly signaling, where standard refinements have no effect. We show that only a Riley-like separating equilibrium is immune to these deviations.
Keywords: C70; C72; 330; Signaling games; Sender-Receiver; robust equilibrium; refinements.; Nichtkooperatives Spiel; Signalling; Spieltheorie; Theorie